Ducks - Endres, Hollie J. (Minneapolis, MN : Bellwether Media, 2008)
Looks at the general characteristics of ducks, and provides information on where they live, what they eat, and how they swim.
Includes bibliographical references (p. 23) and index.
3.3
K-3
Keywords: Ducks -- Juvenile literature; Ducks; Ducks; Ducks